PELATIHAN DAN PENDAMPINGAN PENGGUNAKAN MEDIA PEMBELAJARAN DARING GOOGLE CLASSROOM BAGI GURU DI MASA NEW NORMAL - Dja'wa, Asrianti; Darmanto, Darmanto; Sule, Sani Abdullahi; Abdullah, La Ode Dedi; Abdullah, Rudi; Nilma, Weni Laysa (Jurnal Pengabdian Masyarakat Berkarya, 2024)
In the post Covid 19 pandemic New Normal era, the learning system in Indonesia has changed from a face-to-face classroom system to a hybrid learning system, which is a learning method that combines the concept of online learning with face-to-face learning or PTM. This is done in order to maintain the quality of education in schools in accordance with the mandate of the 1945 Constitution. One of the online learning methods that are widely used by schools is google classroom. Research on the use of Google classroom as an online learning media has been conducted with satisfactory results. The target audience in this service is teachers of SMP Negeri 2 Tomia, Wakatobi Regency, Southeast Sulawesi. In the initial survey of the target audience, the team found that there were obstacles in the audience, namely the target audience had not mastered the use of Android / smartphone and laptop for online learning. So far, the target audience has only used online methods by using whatsapp groups to send materials and students collect assignments to school so that there is still contact between the target audience and students when collecting assignments. Based on these problems, the service team chose to provide training and assistance in online teaching using Google Classroom to overcome the problems of the target audience. The results obtained were very satisfying because they exceeded the achievement target of 99 percent from the initial target of 80 percent for mastering the use of Google classroom as an online learning media for teachers of SMP Negeri 2 Tomia, Wakatobi Regency, Southeast Sulawesi.